PERHITUNGAN VOLUME HIDROKARBON BERDASARKAN DATA GEOKIMIA PADA LAPISAN SERPIH FORMASI SINAMAR, SUMATRA - M. H. Hermiyanto Zajuli (Pusat Survei Geologi, 2011)
Research area located at northwestern part of South Sumatra Basin, occupies 8% of the Â total distribution of Sinamar Formation. The Oligocene Sinamar Formation consists of shale, claystone, mudstone, sandstone, conglomeratic sandstone, and intercalation of coal seams. This research was focused on fine clastic sediments of the Sinamar Formation, such as shale, claystone, and mudstone. Based on the analysis results of source rock richness and maturity, shale of the Sinamar Formation has a good to excellent degree of richness (2% - 10%) as a source rock. The shale of Sinamar Formation tends Â to produce oil derived from type I kerogen (HI > 600 mg HC/TOC). If the shale of Sinamar Formation has an adequate maturity it will produce oil around 5.02 million barrels, while from the total shale of Sinamar Formation approximately 6.08 billion barrels.Keywords : Sinamar Formation, TOC, HI, kerogen type, Rock-Eval pirolysis, hydrocarbon